Bias in social mobility estimates with historical data: Evidence from Swiss microdata - Giacomin Favre (University of Zurich, Department of Economics, 2019)
This paper explores a variety of potential issues one has to address when estimating intergenerational mobility with historical data. Many studies are potentially affected by bias originating from individuals emigrating and thus dropping out of the sample, missing information on the life-cycle, and imperfectly linking data sets. Unique panel data on Zurich's citizenry between 1799 and 1926 entail information on true intergenerational links, and allow to follow individuals across the globe and time. This information enables me to explore how father-son mobility estimates are affected by excluding emigrating individuals, occupational patterns over the life-cycle, and linking procedures. The results suggest that focusing on geographically immobile individuals might decrease the estimated level of social mobility. The estimated level of mobility depends on both the father's and the son's age at classification but does not exhibit a monotone trend in the direction of the bias. Most recent linking procedures do not generate significant bias in the sample of Zurich citizens due to the high level of detail of the data combined with a small population size.
Keywords: J62; J61; N33; N34; 330; DCC; social mobility; geographic mobility; life-cycle; matching; historical data